The Manifestations Of The Duality Of The Sacred And The Profane In The Dreams Of Al-wahrani - louali, Souad (El Omda in Linguistics and Discourse Analysis, 2022)
Text is prose old Algerian mirror reflective of the spirit of the times and the values of society, especially the art of dreams that excelled where Wahrani was so one aspect of beauty creative in the balance of humanity through which the writer about the critical situation in which he lived community during the fifth century Islamic Therefore I sought through this product prose literary formations to break up the narrative structure Mnamat Wahrani in order to shed light on the image to access the sacred and the profane to determine the pattern of social, cultural and silent monitoring